The comparative analysis of women's status in labor relations in modern Slovakia and the Czech Republic - Juraj Hamul'ák; Lenka Freel; Denisa Nevická (DANUBE: Law, Economics and Social Issues Review, 2020)
In this article, the authors deal with the issue of the women's status in labor relations both in the Czech Republic and Slovakia. The authors examined the regulation of the position of women in labor law regulations and compared their results, trying to answer the main question - In which state is it better to work for women after the break-up of Czechoslovakia? Methods of analysis, comparison and synthesis were used. By examining scientific texts and legislation, were the authors able to articulate comprehensive conclusions, not only from the labor law perspective, but also taking into consideration antidiscrimination regulations. The authors reached a conclusion that labor regulations in the Czech Republic are slightly more favorable for women than in the Slovak Republic.
Keywords: 330; Women; Employer; Employee; Labor Relations; Dependant Work